Martian ionosphere observed by MAVEN. 3. Influence of solar wind and IMF on upper ionosphere. (1st October 2018) - Dubinin, E.; Fraenz, M.; Pätzold, M.; McFadden, J.; Halekas, J.S.; Connerney, J.E.P.; Jakosky, B.M.; Vaisberg, O.; Zelenyi, L.
Abstract: In two previous papers (Dubinin et al., 2016, 2017a) we studied the influence of the crustal magnetic field and solar irradiance on the upper ionosphere of Mars based on the observations made on Mars Express. Here we discuss effects of solar wind and the interplanetary magnetic field using the MAVEN observations. It is shown that the upper ionosphere at solar zenith angles ≥ ∼ 40 o and altitudes above ∼ 350 − 400 km is asymmetrical along the direction of the motional electric field. In the hemisphere, in which the motional electric field is directed toward the planet, the ionosphere is denser and expands to higher altitudes as compared to the ionosphere in the opposite hemisphere. The difference in the density of O + and O 2 + ions in both hemispheres achieves almost one order. Such a difference arises due to a different ion convection. Ion convection in both ionospheres occurs in the same direction as the motion of the shocked solar wind in the adjacent magnetosheath although with very different velocities. The upper ionosphere is also sensitive to the variations in the solar wind dynamic pressure, solar wind flux and the value of the motional electric field with a distinct depletion at altitudes above ∼ 450 − 500 km with increase of these solar wind characteristics. The depletion is accompanied by an increase in the horizontal ion velocities. As a result, the ion fluxes to the tail only insignificantly vary with the modest variations of the solar wind characteristics. Highlights: Upper ionosphere of Mars is asymmetrical along the direction of the motional electric field. In the hemisphere, in which the motional electric field is directed toward the planet, the ionosphere is denser and expands to higher altitudes. Upper ionosphere is also sensitive to solar wind variations. With increase of the solar wind dynamic pressure (flux) or the motional electric field the ionosphere at altitudes above 450–500 km is depleted. Ion fluxes to the tail only insignificantly vary with the solar wind strength.